Education in the home - Bessie Sarah Bourne (My University, 1902)
Introduction: Man is influenced by his environments. He lives for himself in no respect. Material and social surroundings affect his ell being, developing the gifts bestowed upon him by nature either for good or for evil. He cannot acquire a fortune in a desert land or even in a fruitful land, if he lives along; nor can he as an isolated human being ever attain any heights of moral excellence. Having no temptations he requires no will power to resist them, need make no effort for that purity of life which seems so difficult to maintain in some districts. But, throw temptation in his way, surround him with the natural influences that require resistance, and then he who overcomes all obstacles and rises above that will show his strength of character and will earn the respect of his fellow man. It is the same with the young and inexperienced child, and even some adults, as it is with undeveloped Indian. Take the Red man from his home, place him in school. He will soon take up the habits of the people with whom he associates. He is taught the ways of the white man. Let him return to his people after finishing his education and more than fifty percent of them go back to the blanket and the habits of their race. The remainder by their efforts to apply their nature to the development of their, rise above the common level and pursue some useful occupation in life.
Citation: Bessie Sarah Bourne. Education in the home. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Education; Home Education; Sociology; Theses; Manuscripts (documents)